Depression in Patients Diagnosed with Type 2 Diabetes Mellitus - Dinorah Janet Torres Lugo; Iván Castillo Ledo; Iriam Rojas Díaz; Antonio Masot Rangel; Silvia Janet Masot Torres; Pedro González López (Revista Finlay, 2022)
Background: during the evolution of diabetes mellitus, chronic complications may appear that affect life expectancy and health-related quality of life, thus harming the physical and mental health of patients. Objective: to determine the behavior of depression in patients diagnosed with diabetes mellitus of the Family Medical Office #21 of the Rodas municipality, Cienfuegos province. Methods: a descriptive cross-sectional study was carried out, in the period from May 2020 to May 2021, the universe and the sample were in correspondence with the 36 diabetic patients dispensed in the office, to whom a survey was applied and the Adult Depression Test. The variables were studied: age, sex, type of treatment, symptoms of depression, complications, level of depression. The analysis and processing of the information was done using the statistical package SPSS version 15 for Windows, the results were expressed in numbers and percentages. Results: predominance of the female sex in 58.3 %, the most represented age group is that of 48-57 (50 %). The group of patients consuming oral hypoglycemic drugs (55 %) predominated. There was a prevalence of patients with depression (72.2 %), being more frequent those receiving treatment with oral hypoglycemic agents (47.2) and there was a high incidence in females (41.6 %). Patients with renal (19.4 %) and cardiovascular (16.6 %) complications predominated. 75 % of the patients presented low depression. Conclusions: the female sex and the age group of 48-57 predominated in the study. There was a high prevalence of complications associated with the appearance of depression and the consumption of oral hypoglycemic agents. More than half of the patients studied presented manifest symptoms of depression. Patients who presented low depression prevailed.